Congenital vulvar teratoma: a case report - I Nyoman Hariyasa Sanjaya; Ryan Saktika Mulyana; Evert Solomon Pangkahila; Hartanto Hartanto (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2020)
Introduction: Teratoma is an embryonal neoplasm consisted of 3 germinal layers. Teratoma usually arises along the line of embryonic cleft and sinus closure formed by the fusion of skin during the embryonic development. In this case report, we present a case of fetal Teratoma on the vulval region, a very rare variant of the disease. Case: A 28-year-old woman came for a routine check-up for her first pregnancy at her 26th weeks of gestational age. On ultrasound examination, a mass was found around the fetal vulva. There was no mass or malformations on other body parts. Placenta and the amount of amniotic fluid were normal. History of congenital anomaly in the family was denied. The patient then gave birth to a female baby at 38 weeks of gestational age without any complication. The baby was healthy, 2650 gram in weight, 50 cm in length, with good APGAR Score (8-10). On the baby left labia, there was a mass measured 5 cm x 4 cm x 3 cm, with slight discoloration. We recommend an early tumor excision to prevent unnecessary complication such as malignant transformation. Although at the time of writing, the patient still waiting for the schedule to remove the tumor due to a non-medical factor. Conclusion: Congenital Teratoma in the vulvar region was a very rare event. First-line therapy is early tumor excision and usually carries an excellent prognosis.